Penanganan Speech Delay pada Anak Usia Dini melalui Terapi Wicara - Fadila Rahmah; Seli Amalia Kotrunnada; Purwati Purwati; Sima Mulyadi (UIN Sultan Maulana Hasanuddin Banten, 2023)
This study discusses the handling that can be done in overcoming speech delay in early childhood. The purpose of this study is to find out various strategies or methods that can be used in stimulating speech delay problems in children from an early age through speech therapy. This study used a qualitative approach with library research method where the subjects of this study reviewed several relevant articles and intended for children aged 4-6 years. The results of this study commonly used speech therapy is to train speaking with correct articulation and practice pronunciation of words slowly and repeatedly. This is very effective to do, because in this word repetition process the child will remember and lock every word that continues to be repeated. The authors recommend that future studies use a type of direct observational research into the field, so that previously found data can be accurately proven with facts in the field.